Metasurfaces: Fundamentals and Applications of Metasurfaces (Small Methods 4/2017). Issue 4 (April 2017) - Hsiao, Hui‐Hsin; Chu, Cheng Hung; Tsai, Din Ping
Abstract : The recent progress in metasurfaces, including the fundamental theoretical background, physical realization, and fabrication, along with their potential practical applications is discussed by Din Ping Tsai and co‐workers in article number 1600064. The outstanding optical properties of metasurfaces have led to the development of versatile ultrathin optical devices such as for beam steering, wave plates, polarimetry, metalenses, metaholograms, and optical vortex beam converters.